Regeional development of Bosnia-Herzegovina - Jasmina Osmanković (European Regional Science Association (ERSA), 2001)
The paper is a research into the regional component in the economic development of bosnia and herzegovina. The regional component is observed, on the one hand, through elaboration of regional issues in the works of bosnian authors, and, on the other, through regional politics in the context of the general development policies of bosnia in the second half of the 20th century. Regional development shold solve major problem for bosnia, which is to facilitate economic functioning of the state as a whole and to create a market on the teritory of the now two divided entities federation Bosnia and Herzegovina and republika srpska without undermining their political integrity. Problem of regional development is that the entities are not and can not function as regions since they have no conditions for exisiting as elements of prosperous regional system. Dayton accords established two regions primarily on the basis of ethnic and political criteria.The system of centers of development is fractured. Studies from 1996 show that it is possible to reestablish the mechanism of regional development which was until 1991. This view is based on the assumed common economic interests in many areas and on the significant possibilities for interregional cooperation.Tho goals of cooperation are free trade, a single market in bosnia, economic development, harmonisation of economic policies, sources of investment and investment politics, joint investments, attracting for foreign capital, adequate urbanisation and functiong of the centers of development, joint ventures in foreign markets in economic and development issues, population policies. The question is how to start off the mechanism. Regional development is an issue of special relevance for bosnia. There is a potential. Regional development has big importance for bosnia, especially for underdeveloped areas.
Keywords: 330